Christian warfare in Rhodesia-Zimbabwe : the Salvation Army and African liberation, 1891-1991 - Murdoch, Norman H. (The Lutterworth Press, 2015)
Christian Warfare in Rhodesia-Zimbabwe takes a hard look at the history of the Salvation Army in Rhodesia-Zimbabwe and its evolving relationship with both the government and the rest of the church. Norman H. Murdoch examines in-depth the parallels between the events of the First Chimurenga, an uprising against European occupation in 1896-97, and the Second Chimurenga in the 1970s, the civil war that led to majority rule. At the time of the first, the Salvation Army was barely established in the country; by the second, it was fully entrenched in the ruling class. Murdoch explores the collaboration of this Christian mission with the institutions of white rule and the painful process of disentanglement necessary by the late twentieth century. Stories of martyrdom and colonial mythology are set in the carefully researched context of ecumenical relations and the Salvation Army's largely unknown and seldom accessible internal politics.--Page 4 of cover.